1997
DOI: 10.1016/s1074-7613(00)80324-6
|View full text |Cite
|
Sign up to set email alerts
|

The Immunoglobulin Class Switch: Beyond “Accessibility”

Abstract: species encoded by different C H genes in the germline (Stavnezer-Nordgren and Sirlin, 1986; Yancopoulos et and Piotr Zelazowski* *Department of Pathology al., 1986). Germline C H RNAs are spliced products of distinct I exons, located 5Ј to every S region, and the The Uniformed Services University of the Health Sciences immediate 3Ј C H gene (Figure 1). Transcription initiates within a promoter 5Ј to the I exon, proceeds through Bethesda, Maryland 20814 † Department of Biochemistry and Cell Biology the S regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
138
0
3

Year Published

1998
1998
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(146 citation statements)
references
References 84 publications
5
138
0
3
Order By: Relevance
“…Thus we have demonstrated that an unidentified component apart from GL transcripts and the switch recombination machinery is necessary for switching. Similar conclusions have been obtained by Mandler et al [41] and have been further discussed in a recent review by Snapper et al [51]. Mandler et al showed that B cells stimulated with anti-IgD antibodies conjugated to dextran in combination with IL-4 produced increased levels of ␥1 transcripts, but failed to switch to IgG1 unless IL-5 was also present.…”
Section: Discussionsupporting
confidence: 79%
“…Thus we have demonstrated that an unidentified component apart from GL transcripts and the switch recombination machinery is necessary for switching. Similar conclusions have been obtained by Mandler et al [41] and have been further discussed in a recent review by Snapper et al [51]. Mandler et al showed that B cells stimulated with anti-IgD antibodies conjugated to dextran in combination with IL-4 produced increased levels of ␥1 transcripts, but failed to switch to IgG1 unless IL-5 was also present.…”
Section: Discussionsupporting
confidence: 79%
“…[33][34][35][36][37][38] There are strains, however, capable of promoting the synthesis of interferon ␥, 33,39-42 a cytokine supporting the production of antibodies of the IgG3 isotype. [43][44][45] The IgG3 isotype, characterizing LACDE BGAL 266-280 /PDC-E2 212-226 cross-reactive antibodies, is noted for its ability to recruit major effectors of tissue damage, such as complement and Fc receptor-bearing cytotoxic cells, [46][47][48] and may have pathogenic implications in PBC. 49 We recognize that if microbes trigger AMA production and ultimately PBC, organisms other than LACDE must be implicated, 10 because the PBC-specific Lactobacillus/ self cross-reactivity observed in the present study is limited to approximately half of the PBC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since its initial discovery (Sen and Gilbert 1988), G4 DNA has been implicated in biological processes such as homologous chromosomal pairing and recombination (Dunnick et al 1993;Frantz and Gilbert 1995;Liu et al 1995). The CAGGG repeats we have described in this study bear a striking resemblance both in sequence and organization to switch recombination signals (Mills et al 1990) that have been shown to mediate genomic rearrangement events that juxtapose immunoglobulin heavy chain variable regions [V(D)J] and constant regions (Snapper et al 1997). The unusual Hoogsteen pairing potential of such guaninerich sequences has been thought to underlie this phenomenon.…”
Section: Genome Research 1053mentioning
confidence: 91%